A Kerr Oscillator based on Counterpropagating Light in a Microresonator - Woodley, Michael T.M.; Hill, Lewis; Del Bino, Leonardo; Oppo, Gian Luca; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
We present experimental and numerical evidence of self-switching behaviours between counterpropagating optical modes in a Kerr microresonator [1]. Switching indicates the restoration on average of symmetry in a previously symmetry-broken state [2] , [3]. The time-evolution of the electric field amplitudes, E ± , of the two counter-propagating modes is accurately described by the following coupled system of ordinary differential equations: equation-dE- ± dt = E-in - [ 1 + i( θ - A| E- ± |ˇ2 - B| E- |ˇ2 ) ]E- ± equation-
CRIS-Team Scopus Importer:2021-10-29